Module 7
Module 7
LESSON 9
INVERSE OF A MATRIX
Learning Outcomes
Recall the concept of a multiplicative inverse in the real number system. For any
nonzero number 𝑎, there exists a number 𝑏 such that 𝑎𝑏 = 𝑏𝑎 = 1. The
number 𝑏 is called the multiplicative inverse of the number 𝑎, and is oftentimes
denoted by 𝑎 −1.
Extending this concept to matrices, for any square matrix 𝑨, there exists a matrix
𝑩 of the same order as 𝑨 such that 𝑨𝑩 = 𝑩𝑨 = 𝑰, where 𝑰 is the identity
matrix. If this is the case, we say that the matrix 𝑨 is nonsingular or invertible.
Also, the matrix 𝑩 is said to be the the inverse of 𝑨.
1. (𝑨−1 )−1 = 𝑨
2. (𝑨𝑩)−1 = 𝑩−1 𝑨−1
3. (𝑨𝑇 )−1 = (𝑨−1 )𝑇
1
𝑨−1 = ( ) (adj 𝑨)
det 𝑨
Example Solve the inverse of the following matrices using the two methods
9.1. discussed above.
1 2
1. 𝑨 = [ ]
3 4
1 2
𝐶12 = (−1)1+2 | |
3 4
= (−1)3 (3)
= −3
1 2
𝐶21 = (−1)2+1 | |
3 4
= (−1)3 (2)
= −2
1 2
𝐶22 = (−1)2+2 | |
3 4
= (−1)4 (1)
=1
𝐶11 𝐶12
Cofactor 𝑨 = [ ]
𝐶21 𝐶22
4 −3
=[ ]
−2 1
1
𝑨−1 = (det 𝑨) (adj 𝑨)
1 4 −2
= (−2) [ ]
−3 1
1 4 −2
= −2[ ]
−3 1
−2 1
=[ 3 −2 ]
1
2
1 2 13 0
[ − 2]
1
0 1 2
𝑅1 ∗ = 𝑅1 − 2𝑅2
1 0 −2 1
[ 3
− 2]
1
0 1 2
2 1 2
2. 𝑨 = [3 4 7]
8 1 −5
2 1 2
det 𝑨 = |3 4 7|
8 1 −5
2 1 2 2 1
= |3 4 7 3 4|
8 1 −5 8 1
(Use basketweave method)
= [2(4)(−5) + 1(7)(8) + 2(3)(1)] −
[2(4)(8) + 2(7)(1) + 1(3)(−5)]
= (−40 + 56 + 6) − (64 + 14 − 15)
= 22 − 63
= −41
2 1 2
(−1)1+2
𝐶12 = | 3 4 7 |
8 1 −5
3 7
= (−1)3 | |
8 −5
= −(3(−5) − 7(8))
= −(−15 − 56)
= 71
2 1 2
𝐶13 = (−1)1+3 | 3 4 7|
8 1 −5
3 4
= (−1)4 | |
8 1
= (3(1) − 4(8))
= 3 − 32
= −29
2 1 2
𝐶21 = (−1)2+1 | 3 4 7 |
8 1 −5
1 2
= (−1)3 | |
1 −5
= −(1(−5) − 2(1))
= −(−5 − 2)
=7
2 1 2
(−1) 2+2
𝐶22 = | 3 4 7 |
8 1 −5
2 2
= (−1)4 | |
8 −5
= (2(−5) − 2(8))
= −10 − 16
= −26
2 1 2
𝐶23 = (−1)2+3 | 3 4 7|
8 1 −5
2 1
= (−1)5 | |
8 1
= −(2(1) − 1(8))
= −(2 − 8)
=6
2 1 2
𝐶31 = (−1)3+1 | 3 4 7 |
8 1 −5
1 2
= (−1)4 | |
4 7
= (1(7) − 2(4))
= (7 − 8)
= −1
2 1 2
𝐶32 = (−1)3+2 | 3 4 7 |
8 1 −5
2 2
= (−1)5 | |
3 7
= −(2(7) − 2(3))
= −(14 − 6)
= −8
2 1 2
𝐶33 = (−1)3+3 | 3 4 7|
8 1 −5
2 1
= (−1)6 | |
3 4
= (2(4) − 1(3))
= (8 − 3)
=5
1
𝑨−1 = (det 𝑨) (adj 𝑨)
−27 7 −1
1
= (−41) [ 71 −26 −8]
−29 6 5
−27 7 −1
1
= − 41 [ 71 −26 −8]
−29 6 5
27 7 1
− 41
41 41
71 26 8
= − 41 41 41
29 6 5
[ − 41 − 41 ]
41
𝑅2 ∗ = 𝑅2 − 3𝑅1
1 1
1 1 0 0
2 2
[0 5
4 − 1
3
0]
2 2
8 1 −5 0 0 1
𝑅3 ∗ = 𝑅3 − 8𝑅1
1 1
1 1 0 0
2 2
[0 5
4 −2 1
3
0]
2
0 −3 −13 −4 0 1
2
𝑅2 ∗ = 𝑅
5 2
1 1
1 1 0 0
2 2
[0 1
8
−5
3 2
0]
5 5
0 −3 −13 −4 0 1
1
𝑅1 ∗ = 𝑅1 − 𝑅2
2
1 4 1
1 0 −5 0
5 5
[0 1
8
−
3 2
0]
5 5 5
0 −3 −13 −4 0 1
𝑅3 ∗ = 𝑅3 + 3𝑅2
1 4 1
1 0 −5 0
5 5
8 3 2
0 1 −5 0
5 5
41 29 6
[0 0 − 5
− 5 5
1]
5
𝑅3 ∗ = − 𝑅
41 3
4 1
1 0
1 −5 0
5
5 3 2
0 1
8 −5 0
5
5 29 6 5
[0 0 1 − 41 − 41]
41
1
𝑅1 ∗ = 𝑅1 − 𝑅3
5
27 7 1
− 41
1 0 0 41 41
8 3 2
0 1 −5 0
5 5
0 0 1 29
−
6
− ]
5
[ 41 41 41
8
𝑅1 ∗ = 𝑅2 − 𝑅3
5
27 7 1
− 41
1 0 0 41 41
71 26 8
0 1 0 − 41 41 41
0 0 1 29 6 5
[ − 41 − 41]
41
𝑨−1 𝑨𝑿 = 𝑨−1 𝑩
(𝑨−1 𝑨)𝑿 = 𝑨−1 𝑩
𝑰𝑿 = 𝑨−1 𝑩 where 𝑰 is the identity matrix
𝑿 = 𝑨−1 𝑩
It is useful to understand some properties of the Identity Matrix, 𝑰.
𝑨𝑰 = 𝑰𝑨 = 𝑨
3. Multiplying a matrix by its inverse results in an identity matrix.
𝑨𝑨−1 = 𝑨−1 𝑨 = 𝑰
1. 4𝑥 + 3𝑦 = 7
2𝑥 − 5𝑦 = 1
4 3 𝑥 7
[ ][ ] = [ ]
2 −5 𝑦 1
4 3 𝑥 7
where 𝑨 = [ ] , 𝑿 = [𝑦] , and 𝑩 = [ ].
2 −5 1
4 3
det 𝑨 = | |
2 −5
= 4(−5) − 3(2)
= −20 − 6
= −26
For the cofactor matrix,
4 3
𝐶11 = (−1)1+1 | |
2 −5
= (−1)2 (−5)
= −5
4 3
𝐶12 = (−1)1+2 | |
2 −5
= (−1)3 (2)
= −2
4 3
𝐶21 = (−1)2+1 | |
2 −5
= (−1)3 (3)
= −3
4 3
𝐶22 = (−1)2+2 | |
2 −5
= (−1)4 (4)
=4
−5 −2
Cofactor 𝑨 = [ ]
−3 4
−5 −3
adj 𝑨 = [ ]
−2 4
1 −5 −3
𝑨−1 = −26 [ ]
−2 4
5 3
26 26
= [1 2]
13
− 13
Solve for 𝑿.
𝑿 = 𝑨−1 𝑩
5 3
26 7
= [26
1 2 ] [1]
−
13 13
5 3
(7) + (1)
= [26
1
26
2 ]
(7) − (1)
13 13
19
= [13
5]
13
19
𝑥
𝑿 = [𝑦] = [13
5]
13
19 5
Therefore, 𝑥 = 13 and 𝑦 = 13.
2. 𝑎 + 𝑐 = −4
𝑎+𝑏+𝑐 =0
5𝑎 − 𝑏 = 6
1 0 1 𝑎 −4
[1 1 1] [𝑏 ] = [ 0 ]
5 −1 0 𝑐 6
1 0 1 𝑎 −4
where 𝑨 = [1 1 1] , 𝑿 = [𝑏 ] , and 𝑩 = [ 0 ].
5 −1 0 𝑐 6
𝑅3 ∗ = 𝑅3 + 𝑅2
1 0 1 1 0 0
[0 1 0 −1 1 0]
0 0 −5 −6 1 1
1
𝑅3 ∗ = − 𝑅3
5
1 0 1 1 0 0
[0 1 0 −1 1 0]
6 1 1
0 0 1 −5 −5
5
𝑅1 ∗ = 𝑅1 − 𝑅3
1 1 1
1 0 0 −5 5 5
[0 1 0 −1 1 0]
6 1 1
0 0 1 −5 −5
5
1 1 1
−5 5 5
−1
𝑨 = [−1 1 0]
6 1 1
5
−5 −5
Solve for 𝑿.
𝑿 = 𝑨−1 𝑩
1 1 1
−5 −4
5 5
= [−1 1 0] [ 0]
6 1 1
−5 − 6
5 5
1 1 1
− 5 (−4) + 5 (0) + 5 (6)
= [ −1(−4) + 1(0) + 0(6) ]
6 1 1
(−4) − (0) − (6)
5 5 5
2
= [ 4]
−6
𝑎 2
𝑿 = [𝑏 ] = [ 4 ]
𝑐 −6
[𝑨] [3 3 2 3
] + [𝑨] = [ ]
4 5 5 1
[𝑨] [3 3 1 0 2 3
] + [𝑨] [ ]=[ ]
4 5 0 1 5 1
[𝑨] ([3 3 1 0 2 3
]+[ ]) = [ ]
4 5 0 1 5 1
[𝑨] [4 3 2 3
]=[ ]
4 6 5 1
4 3 −1
Evaluate the inverse matrix [ ] first.
4 6
4 3 1 0
[ ]
4 6 0 1
1
𝑅1 ∗ = 4 𝑅1
3 1
1 0
[ 4 ] 4
4 6 0 1
𝑅2 ∗ = 𝑅2 − 4𝑅1
3 1
1 0
[ 4 ] 4
0 3 −1 1
1
𝑅2 ∗ = 3 𝑅2
1
3
1 4 0
4
[ 1 1]
0 1 −3 3
3
𝑅1 ∗ = 𝑅1 − 4 𝑅2
1 1
1 0 −4
2
[ 1]
0 1 −1
3 3
1 1
4 3 −1 −4
Therefore, [ ] = [ 21 1]
4 6 −3 3